Employment of evolutionary programming technique for load ability enhancement during line outage / Mohd Syaza Jantan - Jantan, Mohd Syaza (2011)
Nowadays the rapid, continuous and increasing demand in electrical power system network especially inductive load has become major caused to the system's strength under stress and critical condition. Indirectly this problem affects the power system's load ability and stability. Optimal value of reactive power support is vital to improve the condition. Insufficient of reactive power support leads to undesirable voltage breakdown as well as transmission line to outage. This paper presents the employment of Evolutionary Programming (EP) to determine the optimal value of reactive power support by specifying the best value of capacitance to improve the load margin (LM) under single line outage. In order to prove the effectiveness of this technique, justification is conducted on the IEEE-30-Bus Reliability test system. The result revealed that the technique used is capable to improve the LM in contingency condition.